Enhancing Patient Safety and Patient-Centered Care Through Patient and Family Engagement in Hospitals - Tombong, Andi Baso (Faculty of Nursing, Universitas Hasanuddin, 2025)
Patient safety remains a pressing global concern, with millions of preventable adverse events occurring annually, particularly in low-income and middle-income countries. This perspective review highlights the critical role of Patient and Family Engagement (PFE) in enhancing patient safety and advancing patient-centered care in hospital settings. Drawing on global frameworks such as the WHO Global Patient Safety Action Plan 2021–2030 and national policies from countries including the United States, United Kingdom, Australia, and Indonesia, this article underscores the ethical and practical imperatives of involving patients and families as active partners in care. Evidence shows that PFE improve communication, reduce hospital readmissions, enhance treatment adherence, and contribute to better health outcomes. Despite its proven benefits, PFE remains underutilized owing to systemic barriers such as hierarchical communication, limited staff training, and cultural norms. This article calls for a multidimensional approach to embed PFE into hospital practices, including policy reform, education, and leadership support. Future research is recommended to explore practical strategies for implementing PFE and engage all stakeholders in fostering safer, more responsive healthcare systems.